Women we do not talk about: philanthropy e and practices of oblivion and memory (Tempo e Argumento, 2024)
This article discusses the engagement of elite, conservative women in philanthropic and charitable organizations, based on two historical processes that reveal the oscillatory nature of Historiography between oblivion and memory towards these women and their deeds. Firstly, the article discusses two historical processes: the one of feminization of goodwill, charity and philanthropy in Western European and American countries — which was intensified after the 19th century —; and, in turn, the one of contribution to the oblivion of these women’s work, based on the criticism by liberals and socialist Marxists about philanthropy. Both processes shed light on the vast — and under-researched — documentation produced by these women as well as on the scope of their work, which is manifold in terms of social and cultural differences. Secondly, the article discusses the same oscillatory process but in the Brazilian context. If, on the one hand, there was, traditionally, negligence and oblivion towards the history of female social service and assistance in Brazil, on the other hand, since the 1990s, there has been a vigorous and consistent historiographical production about that subject. This production debates the political, social and public agency of women, recognizing not only patterns of social reproduction and adequacy, but also possibilities of broadening the scope of this agency in order to encompass social policies, the defense of women’s rights and even the defense of feminism.
Keywords: philanthropy; memory; oblivion; conservatism